Obtenção e caracterização molecular e fisiológica de plantas de soja contendo o gene AtGolS2 sob déficit hídrico - Honna, Patrícia Teruko [UNESP] (2015)
With the current scenario of climate change, there is a tendency to longer and recurrent drought events, thus obtaining more drought tolerant plants figure as a major investment in the national science and technology. Raffinose family oligosaccharides (RFOs) plays multiple functions in plants and it is known that these are accumulated in plant tissues in water deficit situations, guaranteeing the stability of cell membranes, thus maintaining the vital functions of the plant. In turn, galactinol synthase (GolS, EC 2.4.1.123) catalyzes the first step in the biosynthesis of RFOs plays an important regulatory role in carbon partitioning between sucrose and orphans. Thus, our objective was to introduce gene construction 35S:AtGolS2 via Agrobacterium tumefaciens in soybean plants and characterize molecularly and physiologically events obtained under water deficit. In this context, the conventional soybean BRS 184 was used in the transformation process and the soybean events were molecularly characterized in regard to the transgene copy number by qPCR technique. For the analysis of constitutive gene expression total RNA of events, well-watered conditions, was extracted and the expression determined by RT-qPCR. The segregation rate was calculated using the X2 test (p ≤ 0.05). Based on our results, two events (2Ia1 and 2Ia4) were selected to be analyzed for physiological responses under drought simulated under greenhouse conditions. The results showed that the plants 2Ia4 event the largest accumulation of water associated with lower leaf area in the control condition led to maintenance of gas exchange caused by the reduction in leaf transpiration, increased water accumulation in the substrate and accumulation of raffinose and galactinol transcripts in tissues. Thus, the increased levels of these carbohydrates would have made these act as osmoprotectors, enabling the recommendation of 2Ia4 plants breeding programs aimed at tolerance to drought